Impact of financial integration on economic development, foreign direct investment on CO² emissions and economic growth on foreign capital inflows - Abdullahi, Abubakar (2021)
Financial integration, CO2 emissions, economic development, and institutions are topical issues, which attract interest from academicians and policymakers. The last three decades have seen a significant increase in the degree of financial integration, and therefore crossborder financial flows. Economic development amongst countries has increased likewise. Also, FDI inflows amongst countries has increased substantially while carbon emissions still pose great global environmental challenge. Again, in spite of the low growth rate of GDP relative to the developing and emerging countries, developed nations account for about ninety percent of foreign capital inflows. This study has three specific objectives. The first objective investigates the impact of financial integration on economic growth using data from 2000-2015 in a sample of 95 developed and developing countries using the dynamic panel quantile technique. The results show that the impact of financial integration on economic development varies across income levels. The study finds that financial integration has a negative impact on economic development in low and high-income quantiles, but has no significant impact amongst middle-income quantiles. The second objective examines the impact of foreign direct investment on the emissions of carbon dioxide (CO2) using data from 1995-2014 in a sample of 123 countries at different levels of economic development, using the biascorrected least square dummy method. This results show that FDI has an asymmetry impact on CO2 emissions. FDI reduces CO2 emissions in high and upper-middle-income countries but increases the emissions in low-income countries. The results suggest that FDI flows into high and upper-middle-income countries and attracts cleaner technologies, while the low-income countries become the destination for dirty FDI. The third objective focuses on the moderating role of institutional quality on economic growth-foreign capital inflow nexus, using data from 2002-2015 in a sample of 163 countries, based on the bias-corrected least square dummy variable technique. The results show that economic growth, real income per capita, and foreign reserve have an impact on foreign capital inflow. The study finds the effect of economic growth on capital inflow to be conditional on institutional quality. Economic growth does not influence foreign capital inflow at a low level of institutional quality but has a significant positive effect on capital inflow at median and high level of institutional quality. Economic development is one cardinal global issues, which therefore emphasized the importance of financial integration to augment for domestic capital deficit necessary to realize the growth and developmental aspirations of countries. Therefore, we recommend that countries should pay consideration attention to its trade structure in order to neutralise the impact of financial integration and to promote growth and development. Another central global problem is that of global warming and therefore environmental sustainability through reduction of CO2 emissions. The role of FDI has been stressed in promoting sustainable environment. Secondly, we recommend policy makers especially in developing countries should strengthen their institutions to ensure and enforce compliance to environmental regulations. Thirdly, we recommend that countries wishing to attract foreign capital should focus, amongst other things, on improving institutional variables.